Malaysia newspapers portrayal of 13th general election: The case of political transformation plan era - Ahmad, Mohd Khairie; Mohd Hadza @ Othman, Mohd Baharudin (2013)
Political Transformation Plan (PTP) is an integrated and visionary plan push by the sixth Prime Minister of Malaysia, Najib Razak to transform Malaysia into a truly developed nation by 2020.Since then, the biggest transformation and regarded as Najib's boldest step in political reform was the repealing or amended preventive laws long deemed as draconian, such as the Internal Security Act (ISA), the Printing Presses and Publications Act (PPPA) and several emergency declarations. Those actions been regarded as supporting healthy freedom of speech and press freedom in Malaysia.However to what extend these reform has been translated into meaningful practices of Malaysia‟s newspaper is an interesting and very significance to understand? Generally this paper aim to assess to what extent the current political transformation has impact political reporting by Malaysia newspapers. For that, Malaysia 2013 General Election (GE13) is choosing as the case study.In particular, this study will identify how the political parties have been portrayed? Have they been fairly covered? Thus the coverage of Malaysia 2013 General Election by two Malaysia main newspapers was analysed.The Star (including Sunday Star) and Harian Metro (including Metro Ahad) were chosen as the study samples based on their circulation volume.The GE13 portrayal of these newspapers of the two weeks campaign period was content and thematic analyse using qualitative data analysis software, NVivo10. The content analysis output of this study provides some indicators on the PTP and the trend on Malaysia's newspaper political reporting in PTP era.